Fungal biotransformation of the antihistamine azatadine by Cunninghamella elegans. - Zhang, D (1996)
The metabolism of the antihistamine azatadine by the zygomycete fungus Cunninghamella elegans ATCC 9245 was investigated. Within 72 h from the addition of the drug to 48-h-old cultures grown in Sabouraud dextrose broth, 95% of azatadine was biotransformed. Two major metabolites, 7-hydroxyazatadine (25%) and 8-hydroxyazatadine (50%), and two minor metabolites, N-desmethylazatadine and 9-hydroxyazatadine, were isolated by high-performance liquid chromatography and characterized by mass spectrometric and proton nuclear magnetic resonance spectroscopic analyses.